2019
DOI: 10.1002/ecs2.2580
|View full text |Cite
|
Sign up to set email alerts
|

Growth and quality of Fagus sylvatica saplings depend on seed source, site, and browsing intensity

Abstract: 2019. Growth and quality of Fagus sylvatica saplings depend on seed source, site, and browsing intensity.Abstract. Local climate and ungulate browsing are two major factors that affect tree regeneration and genetic adaptation in Central European forests. Owing to climate change and increasing ungulate numbers, the abiotic and biotic environments of trees are changing remarkably, making it necessary to investigate the separate and joint effects of seed source (i.e., location of tree population origin) and ungul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
(101 reference statements)
1
4
0
3
Order By: Relevance
“…Our results may suggest that the heat treatment may have caused elevated photosynthesis, as warmer temperatures increase the photosynthetic processes that are associated with light [52], and that this was not invested in growth but led to an increased starch accumulation that was exploited in the following years, resulting in an enhanced post-stress growth. An analogous result was found in a simulated browsing experiment on beech saplings, where a single experimental removal of terminal buds was compensated by increased growth (in comparison to the control) in the following year [53]. Additionally, in black oak, carbohydrate storage was shown to be favored relative to growth upon experimental defoliation [54], supporting the hypothesis of enlarged stress induced carbon storage that in its turn can lead to enhanced growth.…”
Section: High Temperature Stress In Early Springsupporting
confidence: 70%
“…Our results may suggest that the heat treatment may have caused elevated photosynthesis, as warmer temperatures increase the photosynthetic processes that are associated with light [52], and that this was not invested in growth but led to an increased starch accumulation that was exploited in the following years, resulting in an enhanced post-stress growth. An analogous result was found in a simulated browsing experiment on beech saplings, where a single experimental removal of terminal buds was compensated by increased growth (in comparison to the control) in the following year [53]. Additionally, in black oak, carbohydrate storage was shown to be favored relative to growth upon experimental defoliation [54], supporting the hypothesis of enlarged stress induced carbon storage that in its turn can lead to enhanced growth.…”
Section: High Temperature Stress In Early Springsupporting
confidence: 70%
“…Our results would be more informative if the experiment had been carried out at two or more locations or even with a fully reciprocal experimental design. However, no interactions between treatment and site were found for morphological traits regarding the recovery of Fagus sylvatica saplings when results from our study sites were compared with those at the lowland study site Birmensdorf (Frank et al, 2019). In addition, a reciprocal common garden experiment can be performed with only a few populations and not with seeds from 90 Abies and 72 Picea seed sources.…”
Section: How Do a Alba And P Abies Saplings React To Simulated Brmentioning
confidence: 83%
“…Very few studies have been conducted to investigate the population differences in recovery following browsing. The growth trait differences in five populations of Pinus sylvestris were found to be maintained irrespective of browsing (O'Reilly‐Wapstra et al, ), and the same was found for saplings of 77 Fagus sylvatica seed sources (Frank, Heiri, & Kupferschmid, ). However, the compensation capacity of tree species in response to leader shoot browsing depends on many factors, among them the architecture of the tree saplings (cf.…”
Section: Introductionmentioning
confidence: 83%
“…These measurements are more difficult with Larix decidua (European larch), Fagus sylvatica (European beech), Quercus petraea (sessile oak), Quercus pubescens (downy oak), Quercus robur (common oak), and Sorbus aucurparia (rowan). This is particularly true for European beech, due to the frequent formation of second to fifth flushes [48]. In principle, it is acceptable to reduce the height increment measurements to one or two preferably browsed main tree species (e.g., silver fir, maple, and ash) and one less frequently browsed species (usually spruce or, depending on the forest type, pine) to estimate the effect of browsing on speciesspecific height growth (Figure 4).…”
Section: Figurementioning
confidence: 99%